Isolation and Analysis of Chemical Components of Essential Oil of Baru Cina (Artemisia vulgaris L) Leaves and Antioxidant Activities Test - Ginting, Adil (Talenta Publisher, 2021)
Essential oil of Baru Cina leaves (Artemisia vulgaris L.) has been successfully isolated by hydrodistillation method using the Stahl apparatus. Baru Cina leaves were hydrodistillation for Â± 6 hours to produce the essential oil amount of 0.39 % (v/b). The essential oil obtained from Baru Cina leaves was characterized by using GC-MS spectroscopy. The GC-MS analysis results showed that there were 29 compounds and the main compounds identified as many as 14 compounds, such as Alpha-Pinene (0.33%), 1,8-Cineol (1.96% ), Filifoline (1.41 %), 1-Octen-3-Ol (2.99 %), 2,4-Cycloheptadien-1-0ne (Eucarvone) (30.61 %), 2-Cyclohexen-1-Ol (Cis) (2.86 %), Bicyclo-3,3,1-Hepta-3-One (1.62 %), Trans-Caryophyllene (4.82 %), 3-Cyclohexen-1-Ol (1, 71 %), 2-Cyclohexen-1-Ol(Trans) (2.75 %), 2-Cyclohexen-1-One (Piperitone) (30.92 %), Trans Carveol (0.31%), Ar-Dimethylphenethyl Alcohol (0.88%), Eugenol (2.42%). This study also showed antioxidant activity from the essential oil of Baru Cina leaves with the IC50 value was 95.76 mg/L.